Famous Malaysian Indians web portal / Jasvinder Kaur Chima Sarandar Singh - Jasvinder Kaur Chima, Sarandar Singh (2004)
The Famous Malaysian Indians web portal is a system created to serve as an informative repository of valuable information. This site would be able to be viewed by anyone who is interested to know about the famous Indian personalities who have achieved fame in fields like sports, law, arts, business, health and politics. This web portal will be incorporated with features like the search engine, voting poll and feedback section. The search engine would prove to be useful for target users like teachers and students. The users would be able to view information about the famous personalities, their pictures, quotable quotes, interviews and articles. The feedback section will enable users to submit their feedback via the feedback form. The voting poll will be useful for the administrators to know how the users judge the web portal so that better service could be provided in future. The development of this site is divided into two main modules which is the user module and the administrator module. The administrator module consists of all the features in the user module but with extra capabilities. They have the authority to add or edit information since they have a username and password. This ensures that the information here is reliable. Research for the literature review was done through the Internet, past thesis documentations and discussions with group members and seniors. Six different existing web sites which are related to the web portal were reviewed.